Wear-resistant antibacterial composite material for rubber plug and preparation method of wear-resistant antibacterial composite material
By using surface-modified carbon-encapsulated silver particles and composite antibacterial agents in the rubber plug material, combined with hydrophobic antibacterial wear-resistant coatings, the shortcomings of traditional rubber plugs in wear resistance and antibacterial properties are solved, and higher wear resistance and antibacterial properties are achieved, extending service life and preventing microbial contamination.
Patent Information
- Application Number
- CN202510019364.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Traditional rubber plugs have significant shortcomings in wear resistance and antibacterial properties, and are prone to wear and contamination in frequent use and humid environments, resulting in degraded sealing performance and damage to product quality.
Wear-resistant and antibacterial composite materials are prepared by vulcanization and plasma treatment, and hydrophobic antibacterial coatings are sprayed on the surface of the material.
The excellent wear resistance and efficient antibacterial properties of rubber plug materials are achieved, which extends the service life and prevents microbial contamination and degradation of sealing performance.
Smart Images

Figure CN119823501A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber preparation, and in particular to a wear-resistant and antibacterial composite material for a rubber stopper and a preparation method thereof. Background Art
[0002] As a key component for sealing various containers, rubber stoppers play an indispensable role in many industries such as chemicals and cosmetics. Whether it is a glass bottle containing corrosive chemical reagents or a delicate container for high-end skin care products, rubber stoppers are responsible for isolating the internal and external environment and maintaining the stability of the contents. The performance of rubber stoppers is closely related to product quality, safety and shelf life. Therefore, the research and development of rubber stopper materials has always been a key topic of great concern in related fields.
[0003] Traditional rubber stoppers are often made of mainstream materials such as natural rubber, nitrile rubber, and silicone rubber. Natural rubber, with its excellent elasticity and flexibility, can fit well into the mouths of various containers and form a tightly fitting seal; nitrile rubber, with its advantages of oil resistance and solvent resistance, performs well in the chemical industry when dealing with corrosion by various chemical substances; silicone rubber occupies a certain market share in medicine and food packaging due to its high and low temperature resistance and good biocompatibility. However, rubber stoppers made of these traditional materials have significant shortcomings in terms of wear resistance and antibacterial properties.
[0004] In actual working conditions, frequent plugging and unplugging and friction are common, such as the frequent use of reagent bottle stoppers in chemical experiments, or the wear of the stoppers caused by frequent opening and trial of cosmetic samples, and the frequent impact of pressure fluctuations inside high-pressure containers on rubber stoppers. These will make ordinary rubber stoppers overwhelmed, and the surface is prone to wear and tear. In severe cases, they may even tear and deform, causing the sealing performance to plummet, resulting in leakage of substances in the container, bringing safety hazards and product losses.
[0005] At the same time, microbial contamination is like a hidden "time bomb" that threatens product quality at all times. During long-term storage of rubber stoppers, especially in a humid environment with high humidity, the rubber material itself has a certain degree of hydrophilicity and is easy to absorb water vapor. In addition, the extremely small amount of nutrient-rich organic matter remaining on the rubber surface during the production and processing process together constitutes a "habitable paradise" in the eyes of microorganisms. Bacteria, fungi and other microorganisms breed and multiply rapidly here. They will not only corrode the rubber stopper itself, damage its structural strength and accelerate aging, but also penetrate the tiny pores of the rubber stopper over time, invade the interior of the container, contaminate the contents, greatly shorten the shelf life of the product, and cause a devastating blow to product quality.
[0006] Although existing rubber plug materials have made many attempts to solve these problems, the results are limited. Conventional rubber formula improvements focus on improving a single performance. For example, simply adding fillers such as carbon black to enhance wear resistance sacrifices rubber flexibility and affects the sealing effect; when adding antibacterial agents, the antibacterial agent often has poor compatibility with the rubber matrix, resulting in precipitation and agglomeration, which weakens the antibacterial durability.
[0007] Therefore, we proposed a wear-resistant and antibacterial composite material for rubber stoppers that has both excellent wear resistance and high-efficiency antibacterial properties and a preparation method thereof. Summary of the invention
[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a wear-resistant and antibacterial composite material for rubber stoppers and a preparation method thereof.
[0009] A method for preparing a wear-resistant and antibacterial composite material for a rubber stopper comprises the following steps:
[0010] S1: Preparation of surface-modified carbon-wrapped silver particles, using silver nitrate and glucose as raw materials to prepare carbon-wrapped silver particles, and then using 3-aminopropyltriethoxysilane to modify the surface of the carbon-wrapped silver particles to obtain a surface-modified carbon-wrapped silver particle dispersion;
[0011] S2: Preparation of a composite antibacterial agent, using benzisothiazolinone, potassium carbonate, N,N-dimethylformamide and 1,3-dibromo-2-propanol to react, followed by purification to prepare an N-substituted benzisothiazolinone compound, and then grafting the N-substituted benzisothiazolinone compound onto surface-modified carbon-coated silver particles to obtain a composite antibacterial agent;
[0012] S3: intercalation modification of zirconium phosphate, using tetrabutyl titanate and polyethyleneimine to intercalate zirconium phosphate to obtain intercalation modified zirconium phosphate;
[0013] S4: Preparation of hydrophobic, antibacterial and wear-resistant coating, polydimethylsiloxane, dilute sulfuric acid, ethyl orthosilicate and silica nanoparticles are mixed, vinyl-substituted polysilsesquioxane and intercalation-modified zirconium phosphate are added, and ultrasonic dispersion is performed to obtain a hydrophobic, antibacterial and wear-resistant coating;
[0014] S5: Preparation of wear-resistant and antibacterial composite materials, adding brominated butyl rubber, ethylene-ethyl acrylate copolymer, polyisobutylene, stearic acid, zinc oxide, sulfur, calcined kaolin, 2,2'-dibenzothiazole disulfide, 2,6-di-tert-butyl-p-cresol and composite antibacterial agent into an internal mixer for mixing, and then vulcanizing to prepare a rubber stopper material, and then plasma treating the rubber stopper material to obtain a pretreated rubber stopper material, spraying a hydrophobic, antibacterial and wear-resistant coating on the surface of the pretreated rubber stopper material, and curing to obtain a wear-resistant and antibacterial composite material.
[0015] Furthermore, the preparation of the surface-modified carbon-coated silver particles in step S1 specifically includes the following steps:
[0016] S1.1: 4-5 parts by weight of 0.3-0.5 mol / L silver nitrate solution is added to 80-90 parts by weight of 0.5 mol / L glucose aqueous solution, and then the solution is transferred into a polytetrafluoroethylene liner, ultrasonically dispersed for 10-20 minutes, and then placed in a closed reactor, reacted at 200-300°C for 5-6 hours, cooled to room temperature, centrifuged, washed, and then dried at 40-50°C for 10-12 hours to obtain carbon-encapsulated silver particles;
[0017] S1.4: Disperse 3-5 parts by weight of carbon-wrapped silver particles in 10-15 parts by weight of ethanol, and ultrasonically disperse for 30-60 minutes to obtain a carbon-wrapped silver particle dispersion. Add 0.3-0.5 parts by weight of 3-aminopropyltriethoxysilane to the carbon-wrapped silver particle dispersion. Under nitrogen protection, stir and react at 60-80°C for 4-6 hours. After the reaction, wash the product with anhydrous ethanol for 2-3 times, and centrifuge to obtain surface-modified carbon-wrapped silver particles. Re-disperse the obtained surface-modified carbon-wrapped silver particles in 10-15 parts by weight of ethanol, and ultrasonically disperse for 30-60 minutes to obtain a surface-modified carbon-wrapped silver particle dispersion.
[0018] Furthermore, the preparation of the composite antibacterial agent in step S2 specifically includes the following steps:
[0019] S2.1: 3-5 parts by weight of benzisothiazolinone and 2-3 parts by weight of potassium carbonate are mixed, and then 20-30 parts by weight of N,N-dimethylformamide is added, and the mixture is stirred at 400-500 r / min for 20-30 min, and then 2-2.3 parts by weight of 1,3-dibromo-2-propanol is added, and the mixture is reacted at 70-73° C. for 14-15 h to obtain a reaction solution;
[0020] S2.2: The reaction solution is cooled to room temperature, and then 40-50 parts by weight of deionized water is added, followed by extraction with ethyl acetate to obtain an organic solution, the organic solution is dried with anhydrous sodium sulfate, and then the filtrate is collected by filtration, and the filtrate is rotary evaporated and purified with a chromatographic column having a ratio of dichloromethane to ethyl acetate of 1:1 to obtain an N-substituted benzisothiazolinone compound;
[0021] S2.3: Add 2-3 parts by weight of an N-substituted benzisothiazolinone compound to 10-12 parts by weight of tetrahydrofuran, stir and mix for 20-30 minutes, then add 0.3-0.5 parts by weight of triethylamine, stir and react at room temperature for 30-60 minutes to obtain a mixed solution;
[0022] S2.4: Add 3-5 parts by weight of the mixed liquid to 10-12 parts by weight of the surface-modified carbon-coated silver particle dispersion, and stir the reaction at 50-70°C for 12-24 hours under nitrogen protection. After the reaction, wash the product with anhydrous ethanol 2-3 times, centrifuge and place it in a vacuum drying oven at 60-80°C for 12-24 hours to obtain a composite antibacterial agent.
[0023] Furthermore, in step S2.2, the structure of the N-substituted benzisothiazolinone compound is:
[0024]
[0025] Furthermore, step S3, the intercalation modification of zirconium phosphate, specifically comprises the following steps:
[0026] S3.1: adding 4-5 parts by weight of zirconium oxychloride to 6-8 parts by weight of deionized water, stirring and mixing for 3-5 minutes to obtain a zirconium oxychloride aqueous solution, adding 8-10 parts by weight of phosphoric acid to 17-20 parts by weight of deionized water, stirring and mixing for 5-10 minutes to obtain a phosphoric acid solution, adding 2-3 parts by weight of polyethyleneimine to 10-12 parts by weight of deionized water, stirring for 3-5 minutes to obtain a polyethyleneimine aqueous solution;
[0027] S3.2: Add 0.06-0.08 parts by weight of tetrabutyl titanate to 5-8 parts by weight of deionized water, stir and mix, then add polyethyleneimine aqueous solution, stir for 3-5 minutes to obtain a mixed solution, then mix the zirconium oxychloride aqueous solution and the phosphoric acid solution and add them to the mixed solution, stir and mix at 700-800r / min for 20-30 minutes, place the obtained solution in a reactor and place it in an oven at 180-200℃ to react for 24-25 hours, then wash the product with distilled water 2-3 times, wash with anhydrous ethanol 2-3 times, and obtain intercalated modified zirconium phosphate after centrifugal drying.
[0028] Furthermore, step S5 of preparing the wear-resistant and antibacterial rubber plug composite material specifically includes the following steps:
[0029] S5.1: Prepare raw materials: 100-120 parts by weight of brominated butyl rubber, 20-30 parts by weight of ethylene-ethyl acrylate copolymer, 2-3 parts by weight of polyisobutylene, 2-3 parts by weight of stearic acid, 3-5 parts by weight of zinc oxide, 0.2-0.3 parts by weight of sulfur, 20-30 parts by weight of calcined kaolin, 1-2 parts by weight of 2,2'-dithiodibenzothiazole, and 1-2 parts by weight of 2,6-di-tert-butyl-p-cresol;
[0030] S5.2: Add the above raw materials and 4-8 parts by weight of the composite antibacterial agent into an internal mixer, mix at 100-110°C for 10-12 minutes to obtain a rubber compound, cool the rubber compound to below 50-60°C, roll it, store it for 24-48 hours, and use an open mixer to produce a sheet at 75-80°C, then cool it to 20-25°C, slice it, and obtain a rubber sheet. Place the rubber sheet in the cavity of a vulcanization mold, and vulcanize it at 170-180°C and 15-18MPa for 3-5 minutes to make a rubber plug material;
[0031] S5.3: Place the rubber stopper material in a plasma treatment device for plasma treatment to obtain a pretreated rubber stopper material, spray a hydrophobic, antibacterial, and wear-resistant coating on the surface of the pretreated rubber stopper material, and then cure it at room temperature for 10-12 minutes to obtain a wear-resistant and antibacterial rubber stopper composite material.
[0032] Furthermore, nitrogen gas is used for plasma treatment in S5.3.
[0033] A wear-resistant and antibacterial composite material for a rubber stopper is prepared by any of the methods for preparing a wear-resistant and antibacterial composite material for a rubber stopper.
[0034] Compared with the prior art, the present invention has at least the following beneficial effects:
[0035] 1. The N-substituted benzisothiazolinone compound synthesized in the present invention has good antibacterial activity. The isothiazolinone ring in its molecular structure is the key part of the antibacterial activity, which can inhibit the growth and reproduction of microorganisms by interacting with microbial cells. In addition, the N-substituted benzisothiazolinone compound chemically reacts with the amino group and other active groups of 3-aminopropyltriethoxysilane on the surface-modified carbon-coated silver particles to achieve grafting. After grafting modification, the carbon-coated silver particles themselves also have certain antibacterial properties. Silver ions can combine with biomacromolecules such as proteins and nucleic acids of microorganisms to destroy the normal physiological functions of microorganisms. Therefore, the combination of the two can produce a synergistic antibacterial effect, so that the composite antibacterial agent has a stronger inhibitory and killing ability against a variety of bacteria, fungi and other microorganisms. At the same time, the carbon-coated silver particles themselves have high strength and hardness. When the composite antibacterial agent is dispersed in the rubber stopper composite material, the carbon-coated silver particles can withstand part of the external force, reduce the deformation and damage of the rubber stopper composite material, and make it difficult to wear the surface during repeated plugging or friction, thereby maintaining the sealing and integrity of the rubber stopper composite material. The 3-aminopropyltriethoxysilane on the surface-modified carbon-coated silver particles can improve the compatibility with the rubber matrix. At the same time, the silane molecules on the surface of the carbon-coated silver particles can increase the steric hindrance between the particles and prevent excessive aggregation between the particles, so that they are evenly dispersed in the rubber matrix, thereby achieving antibacterial persistence.
[0036] 2. The present invention forms titanium dioxide nanoparticles during the hydrolysis of tetrabutyl titanate. These nanoparticles can be inserted into the interlayer of zirconium phosphate to increase the interlayer spacing. Polyethyleneimine is a high molecular weight cationic polymer with good hydrophilicity and adsorption properties. The larger interlayer spacing is conducive to the interaction between polyethyleneimine and the anion layer of zirconium phosphate, thereby realizing the intercalation modification of titanium dioxide and polyethyleneimine into zirconium phosphate. Titanium dioxide has photocatalytic antibacterial properties. Under light conditions, its surface will produce active oxygen species such as hydroxyl free radicals and superoxide anion free radicals with strong oxidizing properties. These active oxygen species can destroy bacterial cell membranes and cells. The cell wall and the internal biological macromolecules can play a bactericidal role. Polyethyleneimine has certain antibacterial properties. The amino group in its molecular structure can interact with the cell membrane of microorganisms and destroy the normal physiological functions of microorganisms. When polyethyleneimine and titanium dioxide are modified into the zirconium phosphate structure through intercalation, the zirconium phosphate can be endowed with antibacterial activity. Polyethyleneimine can form strong interactions with zirconium phosphate and titanium dioxide, such as hydrogen bonds and electrostatic effects, which further enhance the stability of the intercalation structure, making it difficult for the composite material to slip between layers and structural damage when subjected to external friction, thereby improving the wear resistance of the composite material.
[0037] 3. The present invention uses dilute sulfuric acid as a catalyst to prepare an organosilicon polymer through a co-hydrolysis and polycondensation reaction of polydimethylsiloxane and ethyl orthosilicate, and then adds silica nanoparticles, intercalation-modified zirconium phosphate and vinyl-substituted polysilsesquioxane. The prepared hydrophobic, antibacterial and wear-resistant coating has good antibacterial, hydrophobic and wear-resistant effects. The silica nanoparticles added to the coating have a large specific surface area and can adsorb bacteria and restrict their activities. The intercalation-modified zirconium phosphate itself has antibacterial activity and can inhibit and kill adsorbed bacteria. The presence of silica nanoparticles can increase the contact opportunity between bacteria and zirconium phosphate, effectively reducing the risk of bacterial infection during use, and the organosilicon polymer has a low surface energy The characteristics of the coating, as one of the main ingredients in the coating, can significantly reduce the surface energy of the rubber stopper composite material. When the rubber stopper composite material is coated with the coating, it is difficult for water molecules to spread and adhere to its surface, so that the rubber stopper composite material has good hydrophobicity, effectively preventing the penetration and adsorption of liquids such as water and blood, and reducing the bacterial growth and corrosion problems caused by liquid residue. The silica nanoparticles have high hardness and rigidity, and the intercalated modified zirconium phosphate has high hardness and strength. When the rubber stopper composite material rubs against other objects during use, the coating can better resist wear, reduce scratches and wear on the surface of the rubber stopper composite material, and extend the service life of the rubber stopper composite material.
[0038] 4. The present invention introduces vinyl-substituted polysilsesquioxane into the hydrophobic, antibacterial, and wear-resistant coating as a highly active component for enhancing structural stability and adhesion, which can undergo a cross-linking reaction with the active groups on the surface of the intercalated modified zirconium phosphate, thereby better fixing the zirconium phosphate in the coating network structure and enhancing its binding force with the coating system. At the same time, the cross-linked structure also makes it less likely for the coating to have its internal structure destroyed when subjected to friction, thereby improving the wear resistance. In addition, the vinyl-substituted polysilsesquioxane can also enhance the adhesion between the hydrophobic, antibacterial, and wear-resistant coating and the substrate surface and its own physical and chemical stability, thereby achieving a long-lasting hydrophobic, antibacterial, and wear-resistant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.
[0040] Figure 1 The present invention is a flow chart of a method for preparing a wear-resistant and antibacterial composite material for a rubber stopper used in an embodiment of the present invention. DETAILED DESCRIPTION
[0041] The following is a detailed description of the preparation method of a wear-resistant and antibacterial composite material for a rubber stopper provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0042] N-substituted benzisothiazolinone compound structure:
[0043]
[0044] Example 1
[0045] A method for preparing a wear-resistant and antibacterial composite material for a rubber stopper, such as Figure 1 As shown, the following steps are included:
[0046] S1: Preparation of surface-modified carbon-coated silver particles
[0047] S1.1: 4 parts by weight of 0.3 mol / L silver nitrate solution was added to 80 parts by weight of 0.5 mol / L glucose aqueous solution, and then the solution was transferred into a polytetrafluoroethylene liner, ultrasonically dispersed for 10 minutes, and then placed in a closed reactor, reacted at 200°C for 5 hours, cooled to room temperature, centrifuged, washed, and then dried at 40°C for 10 hours to obtain carbon-encapsulated silver particles;
[0048] S1.4: 3 parts by weight of carbon-wrapped silver particles are dispersed in 10 parts by weight of ethanol, and ultrasonically dispersed for 30 minutes to obtain a carbon-wrapped silver particle dispersion liquid, 0.3 parts by weight of 3-aminopropyltriethoxysilane is added to the carbon-wrapped silver particle dispersion liquid, and stirred for reaction at 60° C. for 4 hours under nitrogen protection. After the reaction is completed, the product is washed twice with anhydrous ethanol and centrifuged to obtain surface-modified carbon-wrapped silver particles, and the obtained surface-modified carbon-wrapped silver particles are redispersed in 10 parts by weight of ethanol, and ultrasonically dispersed for 30 minutes to obtain a surface-modified carbon-wrapped silver particle dispersion liquid;
[0049] S2: Preparation of composite antimicrobial agents
[0050] S2.1: 3 parts by weight of benzisothiazolinone and 2 parts by weight of potassium carbonate were mixed, 20 parts by weight of N,N-dimethylformamide were added, and the mixture was stirred at 400 r / min for 20 min, and then 2 parts by weight of 1,3-dibromo-2-propanol were added, and the mixture was reacted at 70° C. for 14 h to obtain a reaction solution;
[0051] S2.2: The reaction solution is cooled to room temperature, and then 40 parts by weight of deionized water is added, followed by extraction with ethyl acetate to obtain an organic solution, the organic solution is dried with anhydrous sodium sulfate, and then the filtrate is collected by filtration, and the filtrate is rotary evaporated and purified with a chromatographic column having a ratio of dichloromethane to ethyl acetate of 1:1 to obtain an N-substituted benzisothiazolinone compound;
[0052] S2.3: Add 2 parts by weight of an N-substituted benzisothiazolinone compound to 10 parts by weight of tetrahydrofuran, stir and mix for 20 minutes, then add 0.3 parts by weight of triethylamine, stir and react at room temperature for 30 minutes to obtain a mixed solution;
[0053] S2.4: Add 3 parts by weight of the mixed solution to 10 parts by weight of the surface-modified carbon-coated silver particle dispersion, and stir the mixture at 50° C. for 12 hours under nitrogen protection. After the reaction, wash the product twice with anhydrous ethanol, centrifuge it, and dry it in a vacuum drying oven at 60° C. for 12 hours to obtain a composite antibacterial agent;
[0054] S3: Intercalation modification of zirconium phosphate
[0055] S3.1: 4 parts by weight of zirconium oxychloride are added to 6 parts by weight of deionized water, and the mixture is stirred for 3 minutes to obtain a zirconium oxychloride aqueous solution; 8 parts by weight of phosphoric acid are added to 17 parts by weight of deionized water, and the mixture is stirred for 5 minutes to obtain a phosphoric acid solution; 2 parts by weight of polyethyleneimine are added to 10 parts by weight of deionized water, and the mixture is stirred for 3 minutes to obtain a polyethyleneimine aqueous solution;
[0056] S3.2: Add 0.06 parts by weight of tetrabutyl titanate to 5 parts by weight of deionized water, stir and mix, then add polyethyleneimine aqueous solution, stir for 3 minutes to obtain a mixed solution, then mix the zirconium oxychloride aqueous solution and the phosphoric acid solution and add them to the mixed solution, stir and mix at 700r / min for 20 minutes, place the obtained solution in a reactor and place it in an oven at 180°C to react for 24 hours, then wash the product twice with distilled water and twice with anhydrous ethanol, and centrifuge and dry to obtain intercalated modified zirconium phosphate;
[0057] S4: Preparation of hydrophobic, antibacterial and wear-resistant coatings
[0058] S4.1: 5 parts by weight of polydimethylsiloxane are added to 20 parts by weight of ethanol, and then 2% of dilute sulfuric acid is added to the system, and the reaction is carried out for 3 hours. Then, 1 part by weight of ethyl orthosilicate is added, and the reaction is carried out for 3 hours. After the reaction is completed, 1 part by weight of silicon dioxide nanoparticles is added, and the mixture is stirred and mixed for 20 minutes to obtain a composite organosiloxane suspension;
[0059] S4.2: Add 1 part by weight of vinyl-substituted polysilsesquioxane to the composite organosiloxane suspension, and then add 0.2 parts by weight of intercalated modified zirconium phosphate again after ultrasonic dispersion for 20 minutes, and then ultrasonic dispersion for 10 hours to obtain a hydrophobic, antibacterial and wear-resistant coating;
[0060] S5: Preparation of wear-resistant and antibacterial rubber plug composites
[0061] S5.1: Prepare raw materials: 100 parts by weight of brominated butyl rubber, 20 parts by weight of ethylene-ethyl acrylate copolymer, 2 parts by weight of polyisobutylene, 2 parts by weight of stearic acid, 3 parts by weight of zinc oxide, 0.2 parts by weight of sulfur, 20 parts by weight of calcined kaolin, 1 part by weight of 2,2'-dithiodibenzothiazole, and 1 part by weight of 2,6-di-tert-butyl-p-cresol;
[0062] S5.2: Add the above raw materials and 4 parts by weight of the composite antibacterial agent into an internal mixer, mix at 100°C for 10 minutes to obtain a rubber compound, cool the rubber compound to below 50°C, roll it up, store it for 24 hours, and use an open mixer to produce a sheet at 75°C, then cool it to 20°C, slice it, and obtain a rubber sheet. Place the rubber sheet in the cavity of a vulcanization mold, and vulcanize it at 170°C and 15MPa for 3 minutes to make a rubber plug material;
[0063] S5.3: Place the rubber stopper material in a plasma treatment device and perform plasma treatment with nitrogen to obtain a pretreated rubber stopper material, spray a hydrophobic, antibacterial, and wear-resistant coating on the surface of the pretreated rubber stopper material, and then cure it at room temperature for 10 minutes to obtain a wear-resistant and antibacterial rubber stopper composite material.
[0064] Example 2
[0065] A method for preparing a wear-resistant and antibacterial composite material for a rubber stopper, such as Figure 1 As shown, the following steps are included:
[0066] S1: Preparation of surface-modified carbon-coated silver particles
[0067] S1.1: 4 parts by weight of 0.3 mol / L silver nitrate solution was added to 80 parts by weight of 0.5 mol / L glucose aqueous solution, and then the solution was transferred into a polytetrafluoroethylene liner, ultrasonically dispersed for 20 minutes, and then placed in a closed reactor, reacted at 300°C for 6 hours, cooled to room temperature, centrifuged, washed, and then dried at 50°C for 12 hours to obtain carbon-encapsulated silver particles;
[0068] S1.4: Disperse 3 parts by weight of carbon-wrapped silver particles in 10 parts by weight of ethanol, and ultrasonically disperse for 60 minutes to obtain a carbon-wrapped silver particle dispersion liquid; add 0.3 parts by weight of 3-aminopropyltriethoxysilane to the carbon-wrapped silver particle dispersion liquid; and stir and react at 80° C. for 6 hours under nitrogen protection; after the reaction, wash the product with anhydrous ethanol for 3 times, and centrifuge to obtain surface-modified carbon-wrapped silver particles; and redisperse the obtained surface-modified carbon-wrapped silver particles in 10 parts by weight of ethanol, and ultrasonically disperse for 60 minutes to obtain a surface-modified carbon-wrapped silver particle dispersion liquid;
[0069] S2: Preparation of composite antimicrobial agents
[0070] S2.1: 3 parts by weight of benzisothiazolinone and 2 parts by weight of potassium carbonate were mixed, 20 parts by weight of N,N-dimethylformamide were added, and the mixture was stirred at 500 r / min for 30 min, and then 2 parts by weight of 1,3-dibromo-2-propanol were added, and the mixture was reacted at 73° C. for 15 h to obtain a reaction solution;
[0071] S2.2: The reaction solution is cooled to room temperature, and then 40 parts by weight of deionized water is added, followed by extraction with ethyl acetate to obtain an organic solution, the organic solution is dried with anhydrous sodium sulfate, and then the filtrate is collected by filtration, and the filtrate is rotary evaporated and purified with a chromatographic column having a ratio of dichloromethane to ethyl acetate of 1:1 to obtain an N-substituted benzisothiazolinone compound;
[0072] S2.3: Add 2 parts by weight of an N-substituted benzisothiazolinone compound to 10 parts by weight of tetrahydrofuran, stir and mix for 30 minutes, then add 0.3 parts by weight of triethylamine, stir and react at room temperature for 60 minutes to obtain a mixed solution;
[0073] S2.4: 3 parts by weight of the mixed solution are added to 10 parts by weight of the surface-modified carbon-coated silver particle dispersion, and the mixture is stirred and reacted at 70° C. for 24 hours under nitrogen protection. After the reaction is completed, the product is washed three times with anhydrous ethanol, centrifuged and dried in a vacuum drying oven at 80° C. for 24 hours to obtain a composite antibacterial agent;
[0074] S3: Intercalation modification of zirconium phosphate
[0075] S3.1: 4 parts by weight of zirconium oxychloride are added to 6 parts by weight of deionized water, and the mixture is stirred for 5 minutes to obtain a zirconium oxychloride aqueous solution; 8 parts by weight of phosphoric acid are added to 17 parts by weight of deionized water, and the mixture is stirred for 10 minutes to obtain a phosphoric acid solution; 2 parts by weight of polyethyleneimine are added to 10 parts by weight of deionized water, and the mixture is stirred for 5 minutes to obtain a polyethyleneimine aqueous solution;
[0076] S3.2: 0.06 parts by weight of tetrabutyl titanate is added to 5 parts by weight of deionized water, and the mixture is stirred and then added with polyethyleneimine aqueous solution, and stirred for 5 minutes to obtain a mixed solution. Then, the zirconium oxychloride aqueous solution and the phosphoric acid solution are mixed and then added to the mixed solution, and the mixture is stirred and mixed at 800 r / min for 30 minutes. The obtained solution is placed in a reactor and placed in an oven at 200°C for reaction for 25 hours. Then, the product is washed with distilled water 3 times and anhydrous ethanol 3 times, and centrifuged and dried to obtain intercalated modified zirconium phosphate;
[0077] S4: Preparation of hydrophobic, antibacterial and wear-resistant coatings
[0078] S4.1: 5 parts by weight of polydimethylsiloxane are added to 20 parts by weight of ethanol, and then 2% of dilute sulfuric acid is added to the system, and the reaction is carried out for 5 hours. Then, 1 part by weight of ethyl orthosilicate is added, and the reaction is carried out for 5 hours. After the reaction is completed, 1 part by weight of silicon dioxide nanoparticles is added, and the mixture is stirred and mixed for 30 minutes to obtain a composite organosiloxane suspension;
[0079] S4.2: Add 1 part by weight of vinyl-substituted polysilsesquioxane to the composite organosiloxane suspension, and then add 0.2 parts by weight of intercalated modified zirconium phosphate again after ultrasonic dispersion for 30 minutes, and then ultrasonic dispersion for 12 hours to obtain a hydrophobic, antibacterial and wear-resistant coating;
[0080] S5: Preparation of wear-resistant and antibacterial rubber plug composites
[0081] S5.1: Prepare raw materials: 100 parts by weight of brominated butyl rubber, 20 parts by weight of ethylene-ethyl acrylate copolymer, 2 parts by weight of polyisobutylene, 2 parts by weight of stearic acid, 3 parts by weight of zinc oxide, 0.2 parts by weight of sulfur, 20 parts by weight of calcined kaolin, 1 part by weight of 2,2'-dithiodibenzothiazole, and 1 part by weight of 2,6-di-tert-butyl-p-cresol;
[0082] S5.2: Add the above raw materials and 4 parts by weight of the composite antibacterial agent into an internal mixer, mix at 110°C for 12 minutes to obtain a rubber compound, cool the rubber compound to below 60°C, roll it up, store it for 48 hours, and use an open mixer to produce a sheet at 80°C, then cool it to 25°C, slice it, and obtain a rubber sheet. Place the rubber sheet in the cavity of a vulcanization mold, and vulcanize it at 180°C and 18 MPa for 5 minutes to make a rubber plug material;
[0083] S5.3: Place the rubber stopper material in a plasma treatment device and perform plasma treatment with nitrogen to obtain a pretreated rubber stopper material, spray a hydrophobic, antibacterial, and wear-resistant coating on the surface of the pretreated rubber stopper material, and then cure it at room temperature for 12 minutes to obtain a wear-resistant and antibacterial rubber stopper composite material.
[0084] Example 3
[0085] A method for preparing a wear-resistant and antibacterial composite material for a rubber stopper, such as Figure 1 As shown, the following steps are included:
[0086] S1: Preparation of surface-modified carbon-coated silver particles
[0087] S1.1: 5 parts by weight of 0.5 mol / L silver nitrate solution was added to 90 parts by weight of 0.5 mol / L glucose aqueous solution, and then the solution was transferred into a polytetrafluoroethylene liner, ultrasonically dispersed for 10 minutes, and then placed in a closed reactor, reacted at 200°C for 5 hours, cooled to room temperature, centrifuged, washed, and then dried at 40°C for 10 hours to obtain carbon-encapsulated silver particles;
[0088] S1.4: Disperse 5 parts by weight of carbon-wrapped silver particles in 15 parts by weight of ethanol, and ultrasonically disperse for 30 minutes to obtain a carbon-wrapped silver particle dispersion, add 0.5 parts by weight of 3-aminopropyltriethoxysilane to the carbon-wrapped silver particle dispersion, and stir and react at 60° C. for 4 hours under nitrogen protection. After the reaction, wash the product twice with anhydrous ethanol and centrifuge to obtain surface-modified carbon-wrapped silver particles, and redisperse the obtained surface-modified carbon-wrapped silver particles in 15 parts by weight of ethanol, and ultrasonically disperse for 30-60 minutes to obtain a surface-modified carbon-wrapped silver particle dispersion;
[0089] S2: Preparation of composite antimicrobial agents
[0090] S2.1: 5 parts by weight of benzisothiazolinone and 3 parts by weight of potassium carbonate were mixed, and then 30 parts by weight of N,N-dimethylformamide were added, and the mixture was stirred at 400 r / min for 20 min, and then 2.3 parts by weight of 1,3-dibromo-2-propanol was added, and the mixture was reacted at 70° C. for 14 h to obtain a reaction solution;
[0091] S2.2: The reaction solution is cooled to room temperature, and then 50 parts by weight of deionized water is added, followed by extraction with ethyl acetate to obtain an organic solution, the organic solution is dried with anhydrous sodium sulfate, and then the filtrate is collected by filtration, and the filtrate is rotary evaporated and purified with a chromatographic column having a ratio of dichloromethane to ethyl acetate of 1:1 to obtain an N-substituted benzisothiazolinone compound;
[0092] S2.3: Add 3 parts by weight of an N-substituted benzisothiazolinone compound to 12 parts by weight of tetrahydrofuran, stir and mix for 20 minutes, then add 0.5 parts by weight of triethylamine, stir and react at room temperature for 30 minutes to obtain a mixed solution;
[0093] S2.4: adding 5 parts by weight of the mixed solution to 12 parts by weight of the surface-modified carbon-encapsulated silver particle dispersion, stirring and reacting at 50° C. for 12 hours under nitrogen protection, after the reaction, washing the product with anhydrous ethanol twice, centrifuging and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a composite antibacterial agent;
[0094] S3: Intercalation modification of zirconium phosphate
[0095] S3.1: 5 parts by weight of zirconium oxychloride are added to 8 parts by weight of deionized water, and the mixture is stirred for 3 minutes to obtain a zirconium oxychloride aqueous solution; 10 parts by weight of phosphoric acid are added to 20 parts by weight of deionized water, and the mixture is stirred for 5 minutes to obtain a phosphoric acid solution; 3 parts by weight of polyethyleneimine are added to 12 parts by weight of deionized water, and the mixture is stirred for 3 minutes to obtain a polyethyleneimine aqueous solution;
[0096] S3.2: Add 0.08 parts by weight of tetrabutyl titanate to 8 parts by weight of deionized water, stir and mix, then add polyethyleneimine aqueous solution, stir for 3 minutes to obtain a mixed solution, then mix the zirconium oxychloride aqueous solution and the phosphoric acid solution and add them to the mixed solution, stir and mix at 700r / min for 20 minutes, place the obtained solution in a reactor and place it in an oven at 180°C to react for 24 hours, then wash the product twice with distilled water and twice with anhydrous ethanol, and centrifuge and dry to obtain intercalated modified zirconium phosphate;
[0097] S4: Preparation of hydrophobic, antibacterial and wear-resistant coatings
[0098] S4.1: 8 parts by weight of polydimethylsiloxane is added to 30 parts by weight of ethanol, and then 3% of dilute sulfuric acid is added to the system, and the reaction is carried out for 3 hours. Then, 2 parts by weight of ethyl orthosilicate is added, and the reaction is carried out for 3 hours. After the reaction is completed, 2 parts by weight of silicon dioxide nanoparticles are added, and the mixture is stirred and mixed for 20 minutes to obtain a composite organosiloxane suspension;
[0099] S4.2: Add 2 parts by weight of vinyl-substituted polysilsesquioxane to the composite organosiloxane suspension, and then add 0.3 parts by weight of intercalated modified zirconium phosphate again after ultrasonic dispersion for 20 minutes, and then ultrasonic dispersion for 12 hours to obtain a hydrophobic, antibacterial, and wear-resistant coating;
[0100] S5: Preparation of wear-resistant and antibacterial rubber plug composites
[0101] S5.1: Prepare raw materials: 120 parts by weight of brominated butyl rubber, 30 parts by weight of ethylene-ethyl acrylate copolymer, 3 parts by weight of polyisobutylene, 3 parts by weight of stearic acid, 5 parts by weight of zinc oxide, 0.3 parts by weight of sulfur, 30 parts by weight of calcined kaolin, 2 parts by weight of 2,2'-dibenzothiazole disulfide, and 2 parts by weight of 2,6-di-tert-butyl-p-cresol;
[0102] S5.2: Add the above raw materials and 8 parts by weight of the composite antibacterial agent into an internal mixer, mix at 100°C for 10 minutes to obtain a rubber compound, cool the rubber compound to below 50°C, roll it up, store it for 24 hours, and use an open mixer to produce a sheet at 75°C, then cool it to 20°C, slice it, and obtain a rubber sheet. Place the rubber sheet in the cavity of a vulcanization mold, and vulcanize it at 170°C and 15MPa for 3 minutes to make a rubber plug material;
[0103] S5.3: Place the rubber stopper material in a plasma treatment device and perform plasma treatment with nitrogen to obtain a pretreated rubber stopper material, spray a hydrophobic, antibacterial, and wear-resistant coating on the surface of the pretreated rubber stopper material, and then cure it at room temperature for 10 minutes to obtain a wear-resistant and antibacterial rubber stopper composite material.
[0104] Comparative Example 1
[0105] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes the composite antibacterial agent in steps S1-S2 and step S5.2, and the other steps remain unchanged to prepare the wear-resistant antibacterial rubber plug composite material, which is recorded as Comparative Example 1.
[0106] Comparative Example 2
[0107] Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes the steps "redispersing the obtained surface modified carbon-coated silver particles in 10 parts by weight of ethanol, ultrasonically dispersing for 30 minutes to obtain a surface modified carbon-coated silver particle dispersion" in steps S2 and S1.4, and replaces the composite antibacterial agent in step S5.2 with an equal mass of surface modified carbon-coated silver particles, and the remaining steps remain unchanged to prepare a wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 2.
[0108] Comparative Example 3
[0109] Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes the intercalated modified zirconium phosphate in step S3 and step S4.2, and the other steps remain unchanged to prepare the wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 3.
[0110] Comparative Example 4
[0111] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes steps S3.1 of "adding 2 parts by weight of polyethyleneimine to 10 parts by weight of deionized water, stirring for 3 minutes, to obtain a polyethyleneimine aqueous solution" and S3.2 of "stirring and mixing and then adding the polyethyleneimine aqueous solution", and the remaining steps remain unchanged to prepare the wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 4.
[0112] Comparative Example 5
[0113] Compared with Example 1, the difference of Comparative Example 5 is that the step "adding 0.06 parts by weight of tetrabutyl titanate to 5 parts by weight of deionized water, stirring and mixing, and then adding polyethyleneimine aqueous solution, stirring for 3 minutes to obtain a mixed solution" in step S3.2 is removed, and the zirconium oxychloride aqueous solution and the phosphoric acid solution in S3.2 are mixed and then added to the polyethyleneimine aqueous solution, and the other steps remain unchanged to prepare the wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 5.
[0114] Comparative Example 6
[0115] Compared with Example 1, the difference of Comparative Example 6 is that Comparative Example 6 removes step S3, step S4 and step S5.3, and the other steps remain unchanged to prepare the rubber plug material, that is, the wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 6.
[0116] Comparative Example 7
[0117] Compared with Example 1, the difference of Comparative Example 7 is that the vinyl-substituted polysilsesquioxane in step S4.2 is removed in Comparative Example 7, and the other steps remain unchanged to prepare the wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 7.
[0118] Comparative Example 8
[0119] Compared with Example 1, the difference of Comparative Example 8 is that Comparative Example 8 removes steps S1 and S2.3-S2.4, replaces the composite antibacterial agent in S5.2 with an N-substituted benzisothiazolinone compound, and the remaining steps remain unchanged to prepare a wear-resistant and antibacterial rubber plug composite material, which is recorded as Comparative Example 8.
[0120] Antibacterial performance test: Shake bottle method: put the wear-resistant antibacterial rubber plug composite material sample into a container containing 5mL nutrient solution and 1×10 7 CFU E. coli and 1×10 7CFU Staphylococcus aureus in a centrifuge tube; placed in a 37°C incubator and shaken for 24 hours; 100 μL of the bacterial solution was taken and the OD value was measured at 600 nm absorbance using an enzyme reader;
[0121] Wear resistance test: Taking EN388:2016 as the reference standard, the Martindale abrasion tester was used to test the wear resistance of the sample. The sample size in the experiment was Φ38mm, the weight of the weight was 9kg, and the end point of the experiment was when a through hole of >1mm appeared in the sample, and the number of wear circles at this time was recorded.
[0122] The antibacterial properties and the number of wear-resistant circles of Examples 1-3 and Comparative Examples 1-8 were measured, and the measurement results are shown in Table 1.
[0123] Table 1. Antibacterial performance and wear resistance circle test results of Examples 1-3 and Comparative Examples 1-8
[0124] Antibacterial rate (%) Wear-resistant circles Example 1 99.99 7484 Example 2 99.99 7529 Example 3 99.99 7503 Comparative Example 1 80.42 6283 Comparative Example 2 84.53 7452 Comparative Example 3 82.34 5382 Comparative Example 4 89.83 6293 Comparative Example 5 87.28 6492 Comparative Example 6 78.43 4293 Comparative Example 7 99.87 6939 Comparative Example 8 82.24 6182
[0125] As can be seen from the data in Table 1, the data of Comparative Examples 1 and 2 are worse than those of the embodiment, indicating that the composite antibacterial agent can improve the antibacterial and wear resistance of the rubber plug composite material when dispersed in the rubber plug composite material. The antibacterial rate of Comparative Example 2 is higher than that of Comparative Example 1, indicating that the N-substituted benzisothiazolinone compound has good antibacterial activity, while the antibacterial rates of Comparative Examples 2 and 8 are significantly lower than those of the embodiment. The N-substituted benzisothiazolinone compound indicates that the combination of the two after the surface-modified carbon-wrapped silver particles are combined can produce a synergistic antibacterial effect. As can be seen from the data of Comparative Examples 3-5, the addition of intercalation-modified zirconium phosphate effectively improves the antibacterial and wear resistance of the rubber plug composite material, and when polyethyleneimine and titanium dioxide are intercalated and modified, the two produce a complementary effect, which can effectively give zirconium phosphate antibacterial activity and improve wear resistance. As can be seen from the data of Comparative Example 6, the hydrophobic antibacterial and wear-resistant coating significantly increases the wear resistance and antibacterial properties of the rubber plug composite material. As can be seen from the data of Comparative Example 7, the introduction of vinyl-substituted polysilsesquioxane can improve wear resistance.
[0126] Long-lasting antibacterial performance test: The samples were stored at room temperature and under ventilated conditions for 365 days, and their antibacterial properties were measured.
[0127] The long-lasting antibacterial performance of Examples 1-3 and Comparative Example 7 was tested, and the test results are shown in Table 2.
[0128] Table 2. Test results of long-lasting antibacterial performance of Examples 1-3 and Comparative Examples 1 and 7
[0129] Persistent antibacterial property (%) Example 1 99.98 Example 2 99.99 Example 3 99.98 Comparative Example 7 77.34
[0130] From the data in Table 2, it can be seen that the introduction of vinyl-substituted polysilsesquioxane can make the rubber stopper composite material achieve long-lasting antibacterial effect, indicating that vinyl-substituted polysilsesquioxane can also enhance the adhesion between the hydrophobic, antibacterial and wear-resistant coating and the substrate surface and its own physical and chemical stability, thereby achieving long-lasting hydrophobic, antibacterial and wear-resistant effect.
[0131] Hydrophobic performance test: The contact angles of the rubber stopper composite materials of Examples 1-3 and Comparative Example 6 were measured on a JCY-2 contact angle meter (Shanghai Fangrui Instrument Co., Ltd.). The measurement results are shown in Table 3.
[0132] Table 3. Hydrophobicity measurement results of Examples 1-3 and Comparative Example 6
[0133] Water contact angle (°) Example 1 132 Example 2 131 Example 3 132 Comparative Example 6 98
[0134] From the data in Table 3, it can be seen that the hydrophobic, antibacterial and wear-resistant coating has a good hydrophobic effect, so that the rubber plug composite material has good hydrophobicity, effectively preventing the penetration and adsorption of liquids such as water and blood, and reducing the bacterial growth and corrosion problems caused by liquid residue.
[0135] The wear-resistant and antibacterial rubber plug composite materials prepared in Examples 1-3 were subjected to puncture tests and sealing tests. The test results are shown in Table 4.
[0136] Table 4. Test results of puncture test and sealing test of Examples 1-3
[0137] Puncture debris (grains), ≤5 (per 100 needles) Self-sealing Adhesion Example 1 1 No penetration No penetration Example 2 0 No penetration No penetration Example 3 1 No penetration No penetration
[0138] It can be seen from the data in Table 4 that the wear-resistant and antibacterial rubber plug composite material prepared by the present invention has good sealing performance.
[0139] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a wear-resistant and antibacterial composite material for a rubber stopper, characterized in that: The steps include: S1: Preparation of surface-modified carbon-wrapped silver particles, using silver nitrate and glucose as raw materials to prepare carbon-wrapped silver particles, and then using 3-aminopropyltriethoxysilane to modify the surface of the carbon-wrapped silver particles to obtain a surface-modified carbon-wrapped silver particle dispersion; S2: Preparation of a composite antibacterial agent, using benzisothiazolinone, potassium carbonate, N,N-dimethylformamide and 1,3-dibromo-2-propanol to react, followed by purification to prepare an N-substituted benzisothiazolinone compound, and then grafting the N-substituted benzisothiazolinone compound onto surface-modified carbon-coated silver particles to obtain a composite antibacterial agent; S3: intercalation modification of zirconium phosphate, using tetrabutyl titanate and polyethyleneimine to intercalate zirconium phosphate to obtain intercalation modified zirconium phosphate; S4: Preparation of hydrophobic, antibacterial and wear-resistant coating, polydimethylsiloxane, dilute sulfuric acid, ethyl orthosilicate and silica nanoparticles are mixed, vinyl-substituted polysilsesquioxane and intercalation-modified zirconium phosphate are added, and ultrasonic dispersion is performed to obtain a hydrophobic, antibacterial and wear-resistant coating; S5: Preparation of wear-resistant and antibacterial rubber stopper composite materials. Bromobutyl rubber, ethylene-ethyl acrylate copolymer, polyisobutylene, stearic acid, zinc oxide, sulfur, calcined kaolin, 2,2'-dibenzothiazole disulfide, 2,6-di-tert-butyl-p-cresol and composite antibacterial agent are added into an internal mixer for mixing, and then vulcanized to prepare a rubber stopper material. The rubber stopper material is plasma treated to obtain a pretreated rubber stopper material, and a hydrophobic, antibacterial and wear-resistant coating is sprayed on the surface of the pretreated rubber stopper material. After curing, the wear-resistant and antibacterial rubber stopper composite material is obtained.
2. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 1, characterized in that: Step S1: Preparation of surface-modified carbon-coated silver particles, specifically comprising the following steps: S1.1: 4-5 parts by weight of 0.3-0.5 mol / L silver nitrate solution is added to 80-90 parts by weight of 0.5 mol / L glucose aqueous solution, and then the solution is transferred into a polytetrafluoroethylene liner, ultrasonically dispersed for 10-20 minutes, and then placed in a closed reactor, reacted at 200-300°C for 5-6 hours, cooled to room temperature, centrifuged, washed, and then dried at 40-50°C for 10-12 hours to obtain carbon-encapsulated silver particles; S1.4: Disperse 3-5 parts by weight of carbon-wrapped silver particles in 10-15 parts by weight of ethanol, and ultrasonically disperse for 30-60 minutes to obtain a carbon-wrapped silver particle dispersion. Add 0.3-0.5 parts by weight of 3-aminopropyltriethoxysilane to the carbon-wrapped silver particle dispersion. Under nitrogen protection, stir and react at 60-80°C for 4-6 hours. After the reaction, wash the product with anhydrous ethanol for 2-3 times, and centrifuge to obtain surface-modified carbon-wrapped silver particles. Re-disperse the obtained surface-modified carbon-wrapped silver particles in 10-15 parts by weight of ethanol, and ultrasonically disperse for 30-60 minutes to obtain a surface-modified carbon-wrapped silver particle dispersion.
3. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 2, characterized in that: Step S2: Preparation of the composite antibacterial agent, specifically comprising the following steps: S2.1: 3-5 parts by weight of benzisothiazolinone and 2-3 parts by weight of potassium carbonate are mixed, and then 20-30 parts by weight of N, N-dimethylformamide are added, and the mixture is stirred at 400-500 r / min for 20-30 min, and then 2-2.3 parts by weight of 1,3-dibromo-2-propanol are added, and the mixture is reacted at 70-73°C for 14-15 h to obtain a reaction solution; S2.2: The reaction solution is cooled to room temperature, and then 40-50 parts by weight of deionized water is added, and then extracted with ethyl acetate to obtain an organic solution, and the organic solution is dried with anhydrous sodium sulfate, and then the filtrate is collected by filtration, and the filtrate is rotary evaporated and purified using a chromatographic column with a ratio of dichloromethane:ethyl acetate of 1:1 to obtain an N-substituted benzisothiazolinone compound; S2.3: Add 2-3 parts by weight of an N-substituted benzisothiazolinone compound to 10-12 parts by weight of tetrahydrofuran, stir and mix for 20-30 minutes, then add 0.3-0.5 parts by weight of triethylamine, stir and react at room temperature for 30-60 minutes to obtain a mixed solution; S2.4: Add 3-5 parts by weight of the mixed liquid to 10-12 parts by weight of the surface-modified carbon-coated silver particle dispersion, and stir the reaction at 50-70°C for 12-24 hours under nitrogen protection. After the reaction, wash the product with anhydrous ethanol 2-3 times, centrifuge and place it in a vacuum drying oven at 60-80°C for 12-24 hours to obtain a composite antibacterial agent.
4. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 3, characterized in that: The structure of the N-substituted benzisothiazolinone compound in step S2.2 is:
5. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 4, characterized in that: Step S3: intercalation modification of zirconium phosphate, specifically comprising the following steps: S3.1: adding 4-5 parts by weight of zirconium oxychloride to 6-8 parts by weight of deionized water, stirring and mixing for 3-5 minutes to obtain a zirconium oxychloride aqueous solution, adding 8-10 parts by weight of phosphoric acid to 17-20 parts by weight of deionized water, stirring and mixing for 5-10 minutes to obtain a phosphoric acid solution, adding 2-3 parts by weight of polyethyleneimine to 10-12 parts by weight of deionized water, stirring for 3-5 minutes to obtain a polyethyleneimine aqueous solution; S3.2: Add 0.06-0.08 parts by weight of tetrabutyl titanate to 5-8 parts by weight of deionized water, stir and mix, then add polyethyleneimine aqueous solution, stir for 3-5 minutes to obtain a mixed solution, then mix the zirconium oxychloride aqueous solution and the phosphoric acid solution and add them to the mixed solution, stir and mix at 700-800r / min for 20-30 minutes, place the obtained solution in a reactor and place it in an oven at 180-200℃ to react for 24-25 hours, then wash the product with distilled water 2-3 times, wash with anhydrous ethanol 2-3 times, and obtain intercalated modified zirconium phosphate after centrifugal drying.
6. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 5, characterized in that: Step S4 is the preparation of a hydrophobic, antibacterial and wear-resistant coating, which specifically comprises the following steps: S4.1: Add 5-8 parts by weight of polydimethylsiloxane to 20-30 parts by weight of ethanol, then add 2-3% of dilute sulfuric acid in the system, react for 3-5 hours, then add 1-2 parts by weight of ethyl orthosilicate, react for 3-5 hours, and after the reaction, add 1-2 parts by weight of silicon dioxide nanoparticles, stir and mix for 20-30 minutes to obtain a composite organosiloxane suspension; S4.2: Add 1-2 parts by weight of vinyl-substituted polysilsesquioxane to the composite organosiloxane suspension, and then add 0.2-0.3 parts by weight of intercalated modified zirconium phosphate after ultrasonic dispersion for 20-30 minutes, and then ultrasonic dispersion for 10-12 hours to obtain a hydrophobic, antibacterial, and wear-resistant coating.
7. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 6, characterized in that: Step S5 is the preparation of the wear-resistant and antibacterial rubber plug composite material, which specifically includes the following steps: S5.1: Prepare raw materials: 100-120 parts by weight of brominated butyl rubber, 20-30 parts by weight of ethylene-ethyl acrylate copolymer, 2-3 parts by weight of polyisobutylene, 2-3 parts by weight of stearic acid, 3-5 parts by weight of zinc oxide, 0.2-0.3 parts by weight of sulfur, 20-30 parts by weight of calcined kaolin, 1-2 parts by weight of 2,2'-dithiodibenzothiazole, and 1-2 parts by weight of 2,6-di-tert-butyl-p-cresol; S5.2: Add the above raw materials and 4-8 parts by weight of the composite antibacterial agent into an internal mixer, mix at 100-110°C for 10-12 minutes to obtain a rubber compound, cool the rubber compound to below 50-60°C, roll it, store it for 24-48 hours, and use an open mixer to produce a sheet at 75-80°C, then cool it to 20-25°C, slice it, and obtain a rubber sheet. Place the rubber sheet in the cavity of a vulcanization mold, and vulcanize it at 170-180°C and 15-18MPa for 3-5 minutes to make a rubber plug material; S5.3: Place the rubber stopper material in a plasma treatment device for plasma treatment to obtain a pretreated rubber stopper material, spray a hydrophobic, antibacterial, and wear-resistant coating on the surface of the pretreated rubber stopper material, and then cure it at room temperature for 10-12 minutes to obtain a wear-resistant and antibacterial rubber stopper composite material.
8. The method for preparing a wear-resistant and antibacterial composite material for a rubber stopper according to claim 7, characterized in that: In S5.3, nitrogen gas is used for plasma treatment.
9. A wear-resistant and antibacterial composite material for a rubber stopper, characterized in that: The rubber stopper is prepared by the method for preparing a wear-resistant and antibacterial composite material for a rubber stopper as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Low emission, high scrub vae latex paints
CN101665647A
Preparation method for high-aging-resistance anti-bacteria medical rubber plug
CN109233121A
Antibacterial and antiviral agent and application thereof in rubber and plastic materials
CN116041792A
High-strength wear-resistant PP material and preparation method thereof
CN118459893A